2018
DOI: 10.1021/acs.jpcc.8b01825
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Bonding of Unique CO on Fe(100)

Abstract: At low coverage, CO molecules are known to preferentially occupy the hollow sites of Fe(100) with considerably inclined molecular orientations. This CO configuration serves as the precursor state of CO dissociation, which is particularly important in several important catalytic reactions. In this study, we present a unique bonding picture of the precursor state from the spin, charge, and orbital perspectives. From the spin and orbital views, we show the antiferromagenetic nature of the adsorbate−metal coupling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 60 publications
1
1
0
Order By: Relevance
“…The 2p x and 2p y states are found to be spin-dependent, although they have different spin-dependent behaviors. These observations are well collaborated with geometric and energetic data as well as Lowdin charges published in 2017 (ref ) and 2018 (ref ). In particular, the data of charges gives us an idea of how substantial these orbital processes and proposed hybridizations are, as it has demonstrated that these orbital processes lead to the attractive carbon end and the repulsive oxygen end.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The 2p x and 2p y states are found to be spin-dependent, although they have different spin-dependent behaviors. These observations are well collaborated with geometric and energetic data as well as Lowdin charges published in 2017 (ref ) and 2018 (ref ). In particular, the data of charges gives us an idea of how substantial these orbital processes and proposed hybridizations are, as it has demonstrated that these orbital processes lead to the attractive carbon end and the repulsive oxygen end.…”
Section: Resultssupporting
confidence: 82%
“…However, transition states are hard to capture because of short lifetimes. Nevertheless, CO adsorption at Fe(100) displays an example that transition-state-like structures of CO bond cleavage are captured by the perfect metal surface, as the elementary reaction of CO dissociation fits into the category of an early barrier reaction where its transition state structurally resembles the unique reactant or adsorbate by simply elongating the C–O bond along the molecular axis. Interestingly, both experiments and density functional theory (DFT) calculations consistently revealed that the unique CO species preferentially have the respective carbon and oxygen atoms simultaneously occupied at the hollow and bridge sites, with considerably inclined molecular orientations. The consensus means the generalized gradient approximation (GGA) level of theory not only provides a qualitatively good picture but a quantitatively correct scenario. Thus, Fe(100) is quite unique because only upstanding CO molecules can be found on other transition metal surfaces.…”
Section: Introductionmentioning
confidence: 99%